Analisis Dinamika Kemiskinan (Poverty Dynamics) Di Bali Berdasarkan Data Susenas Panel 2008 – 2010 - Dariwardani, Ni Made Inna (Jurnal Ekonomi Kuantitatif Terapan, 2014)
Poverty dynamics is associated with the analysis of poverty over time, which examineswho stays, moves into, and moves out of poverty in the given period. Those who stays in poverty from time to time (known as cronic poverty) should be given different policies from those who temporary move out from poverty (transient poverty). Utilizing the 2008, 2009, 2010 Socio Economic Survey (Susenas) panel data, this research examines the poverty dynamics within the regional base which is Bali Province. During the period of 2008 – 2010, about 1,86 percent of total households in Bali suffers cronic poverty. Moreover, in the same period about 8,69 percent of total households in Bali are vulnerable to poverty (transiently poor). Those who cronically poor needs programs that can enhance their human capital such as education and training. Furthermore, those who vulnerable to poverty or transiently poor require programs that can reduce household consumption variability such as cash transfer and insurance.
Keywords: poverty dynamics; chronic poverty; transient poverty; vulnerable to poverty